1983
DOI: 10.1002/qua.560230509
|View full text |Cite
|
Sign up to set email alerts
|

Electronic correlation contribution to the three‐body potentials for water trimers

Abstract: A number of trimers of water molecules have been computed with an extended basis set in the Hartree-Fock and in the direct CI approximations. It has been verified that the three-body interaction energy can be calculated within the Hartree-Fock method. Therefore, the correlation corrections to the Hartree-Fock level are essentially additive and do not contribute'significantly to three-body effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Habitz et al later extended the previous calculations to include configuration interaction, but found that these corrections (which include dispersion terms such as the ATM) contribute little to the total three-body effect in water trimer. 249 Clementi et al later directly fit these three-body effects to the classical polarization analytical form250 and extended this formalism to fourbody terms. 251 The polarization energy (for a model based on bond polarizabilities) is written as ^pol -~2…”
Section: B Aqueous Systemsmentioning
confidence: 99%
“…Habitz et al later extended the previous calculations to include configuration interaction, but found that these corrections (which include dispersion terms such as the ATM) contribute little to the total three-body effect in water trimer. 249 Clementi et al later directly fit these three-body effects to the classical polarization analytical form250 and extended this formalism to fourbody terms. 251 The polarization energy (for a model based on bond polarizabilities) is written as ^pol -~2…”
Section: B Aqueous Systemsmentioning
confidence: 99%
“…Fortunately, four-body and higher order terms are usually negligible [1][2][3][4][5][6][7][8]. This is of particular importance since almost all of molecular modeling procedures ignores non-additive contributions to the total energy of molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, corrections for electron correlation are important contributions to amount of individual n-body terms frequently imposing increase of their magnitudes. On the other hand many-body contributions can substantially vary with the relative orientation of monomers [5,6] and can originate from distinct types of interactions. For example in case of water molecules energies of hydrogen bonding are two order stronger than for van der Waals interactions in noble gas clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Small water clusters have also been the subject of a number of theoretical studies. See ref for a review of some older theoretical work on the dimer. Most of these investigations were restricted to the determination of the most stable structures and the corresponding binding energies and harmonic vibrational frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…A question that was first addressed in a series of pioneering papers by Clementi and collaborators [16][17][18][19][20][21] is the importance of the nonadditive many-body interactions on the properties of liquid water. They included the three-and four-body contributions to the interaction potential that originate from the longrange induction energy, which they obtained from iterative calculations within the bond-polarization model.…”
Section: Introductionmentioning
confidence: 99%